2016
DOI: 10.5430/rwe.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foreign Direct Investment and Economic Freedom on Economic Growth: The Case of BRICS Countries

Abstract: This paper researches the interaction between economic freedom (EF), foreign direct investment (FDI) and economic growth in the five BRICS countries namely, Brazil, Russia, India, China and South Africa over the term 1995-2013. In order to trying the data, panel data analysis is exercised. The results indicate that whole index of EF is positively and acutely associated with economic growth, further, the results indicate that FDI is positively related and statistically significant determinant of economic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The evidence suggested that there was a positive relationship between fiscal as well as financial freedom and economic growth. Similar results were reported in Haydaroglu (2016) for Brazil, Russia, India, China and South Africa (BRICS). Further, Karabegovic et al (2003) and Bennett (2016) observed that the level and growth of economic freedom positively affected GDP level and growth in 10 Canadian provinces and 50 American states over the period from 1994 to 1999 (and 1981 to 1997).…”
Section: Literature Reviewsupporting
confidence: 87%
“…The evidence suggested that there was a positive relationship between fiscal as well as financial freedom and economic growth. Similar results were reported in Haydaroglu (2016) for Brazil, Russia, India, China and South Africa (BRICS). Further, Karabegovic et al (2003) and Bennett (2016) observed that the level and growth of economic freedom positively affected GDP level and growth in 10 Canadian provinces and 50 American states over the period from 1994 to 1999 (and 1981 to 1997).…”
Section: Literature Reviewsupporting
confidence: 87%
“…In the context of BRICS countries, recent studies are undertaken to get a deeper understanding of FDI inflows or outflows determinants. Studies (Haydariuglu, 2016;Kishor & Singh, 2015;Labes, 2015;Popa & Carp, 2013;Ranjan & Agrawal, 2011;Vijaykumar, Sridharan, & Rao, 2010) observed market size, labour cost, infrastructure, currency value, and gross capital formation work as the catalyst to attract FDI inflows in BRICS, while trade openness and inflation turns out insignificant. In a study by Jadhav (2012) to test the determinants of FDI in BRICS, confirmed that traditional economic factors are more significant than the institutional and political factors in promoting FDI into BRICS countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Besides, the obtained outcome showed that economic freedom is a key determinant of effective FDI attracting policy. The conclusion of Hayrdaroglu (2016) is also confirmed by Maryam and Mittal (2020). Recently, Pradhan et al (2019) inspect the linkage between economic growth, stock market depth, trade openness, and FDI in 25 ASEAN regional forum countries.…”
Section: The Interaction Between Foreign Direct Investment and Econommentioning
confidence: 73%